Dynamin‐related protein 1‐mediated mitochondrial fission contributes to IR‐783‐induced apoptosis in human breast cancer cells. Issue 9 (11th July 2018) - Tang, Qin; Liu, Wuyi; Zhang, Qian; Huang, Jingbin; Hu, Changpeng; Liu, Yali; Wang, Qing; Zhou, Min; Lai, Wenjing; Sheng, Fangfang; Li, Guobing; Zhang, Rong
Abstract: IR‐783 is a kind of heptamethine cyanine dye that exhibits imaging, cancer targeting and anticancer properties. A previous study reported that its imaging and targeting properties were related to mitochondria. However, the molecular mechanism behind the anticancer activity of IR‐783 has not been well demonstrated. In this study, we showed that IR‐783 inhibits cell viability and induces mitochondrial apoptosis in human breast cancer cells. Exposure of MDA‐MB‐231 cells to IR‐783 resulted in the loss of mitochondrial membrane potential (MMP), adenosine triphosphate (ATP) depletion, mitochondrial permeability transition pore (mPTP) opening and cytochrome c (Cyto C) release. Furthermore, we found that IR‐783 induced dynamin‐related protein 1 (Drp1) translocation from the cytosol to the mitochondria, increased the expression of mitochondrial fission proteins mitochondrial fission factor (MFF) and fission‐1 (Fis1), and decreased the expression of mitochondrial fusion proteins mitofusin1 (Mfn1) and optic atrophy 1 (OPA1). Moreover, knockdown of Drp1 markedly blocked IR‐783‐mediated mitochondrial fission, loss of MMP, ATP depletion, mPTP opening and apoptosis. Our in vivo study confirmed that IR‐783 markedly inhibited tumour growth and induced apoptosis in an MDA‐MB‐231 xenograft model in association with the mitochondrial translocation of Drp1. Taken together, these findings suggest that IR‐783 induces apoptosis in human breast cancer cells by increasing Drp1‐mediated mitochondrial fission. Our study uncovered the molecular mechanism of the anti‐breast cancer effects of IR‐783 and provided novel perspectives for the application of IR‐783 in the treatment of breast cancer.